Smart Parenting dalam Mengatasi Social Withdrawal pada Anak di Pondok Pesantren (Ta'allum: Jurnal Pendidikan Islam, 2019)
Smart Parenting is a pattern of education strategies for children, where parents as madrasatul ula (the first educators) in nurturing and guiding child development. The principle of Smart Parenting what is good for parents is good for children too. It make no problem in the process of child development such as social withdrawal. Social Withdrawal will arise when children experience stress and feel depressed in their lives. This problem is rampant among children, especially among "santri". This study uses a qualitative approach as well ad phenomenological approach in pesantren Nurul Jadid located in Probolinggo Regency. Nurul Jadid’s regulation which limits santri’s space of movement implicates many problem and phenomena in it, so early handling of Social Withdrawal is need to prevent the other problems anda phenomena.  The results of the study showes that pesantren Nurul Jadid applies five smat parenting concept as antidotes for santri who experiences social withdrawals. The five concepts consists of; Responding, Monitoring, Mentoring, Modeling and Defense. The implication is that the foster mother can easily deal with santri who experiences Social Withdrawal in Nurul Jadid Islamic boarding school.
Keywords: Smart Parenting; social withdrawal; pesantren